STRATEGI PEMERINTAH DAERAH DALAM MENGEMBANGKAN PARIWISATA BERKELANJUTAN - Bhayu Rhama (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2020)
ABSTRACT This study is aimed to describe and analyse the strategies of local governments in developing sustainable tourism in Sebangau Subdistrict, Palangka Raya. This research is a qualitative research to obtain a comprehensive and in-depth picture related to the problem and collects primary data from the Culture and Tourism Office of Palangka Raya City, tourist attractions in Sebangau District, and local communities around the Sebangau District tourist area. Data sources are also obtained from secondary data such as archives or library materials that are used as support. Data collection is done using observation, interviews, and documentation. Analysis of research data is carried out through stages which include data reduction, data exposure, and drawing conclusions / verification. The study shows that the strategy of the local government of Palangka Raya in developing sustainable tourism in Sebangau District is carried out on the development of human and natural resources. Human resource development strategies include education development, health development, improving the quality of the poor, and suppressing the rate of population growth. One-way natural resource development strategies include the development of tourism areas that are only carried out in a small area, tourism development is also carried out by not changing the landscape base, as well as the construction of tourist infrastructure in accordance with local identity. Supporting factors for sustainable tourism development strategies are awareness of the local community about the importance of the tourism area. The role of relevant parties who participated in encouraging the development of sustainable tourism. While the inhibiting factors of the strategy for developing sustainable tourism is to provide a deeper understanding of tourism to the community. In addition, budget limitations are also the second limiting factor in sustainable tourism development   Keywords: Sustainable tourism, development, strategy, local government